Handbook of Psychology 2003
DOI: 10.1002/0471264385.wei0520
|View full text |Cite
|
Sign up to set email alerts
|

Social Conflict, Harmony, and Integration

Abstract: This chapter examines psychological perspectives on intergroup relations, their implications for reducing bias and conflict, and their potential applications for enhancing social integration. Psychological research on social conflict, harmony, and integration has adopted one of two general perspectives. One perspective places an emphasis on functional relations between groups, typically pointing to competition and consequent perceived threat as a fundamental cause of intergroup prejudice and conflict (e.g., re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…Brewer (1979Brewer ( , 2007 has proposed that positive responses to the ingroup and negative responses to outgroups are separable and that, in the absence of competition or conflict (Dovidio, Gaertner, Mayville, & Perry, 2013), relations with ingroup members are of primary importance. This perspective suggests that the effects of just world beliefs, particularly in terms of responses to outgroup members, may be critically determined by the nature of intergroup relations.…”
Section: Discussionmentioning
confidence: 99%
“…Brewer (1979Brewer ( , 2007 has proposed that positive responses to the ingroup and negative responses to outgroups are separable and that, in the absence of competition or conflict (Dovidio, Gaertner, Mayville, & Perry, 2013), relations with ingroup members are of primary importance. This perspective suggests that the effects of just world beliefs, particularly in terms of responses to outgroup members, may be critically determined by the nature of intergroup relations.…”
Section: Discussionmentioning
confidence: 99%
“…
repeated personalized contacts with a variety of outgroup members should, over time, undermine the value and meaningfulness of the social category stereotype as a source of information about members of that group. This is the process by which contact experiences are expected to generalize – via reducing the salience and meaning of social categorization in the long run (Dovidio et al ., 2003, p. 493).
…”
Section: Political Socialization In An Age Of Diversitymentioning
confidence: 99%
“…But many scholars observed that inter-caste marriages promote honor killing and crimes against the Dalit community and lower castes if the caste amalgamation occurs by violating the social norms (Tamalapakula, 2019;Gupta, 2014, Goli, Singh, &Sekher, 2013Srinivasan, 2016). These situations promote disharmony and discontent in the Indian society which is strictly associated with the Caste phenomenon (Dovidio et al, 2013;Parish, 2016;Wilkerson, 2020;Sundiata, 2021).…”
Section: Caste and Disharmonymentioning
confidence: 99%